Obscure locks, simple keys : the annotated Watt - Ackerley, Chris, 1947- (Edinburgh University Press, 2010)
Obscure Locks, Simple Keys is a comprehensive study of Samuel Beckett's most enigmatic text, Watt. Chris Ackerley's approach, which is similar to genetic editing, extensively reads the novel's different editions and manuscripts (including the French translation, overseen by Beckett himself), and his long introduction engages with the complex history of the book's making. One appendix deals with textual changes and errata in major editions of the novel, and the other confronts the novel's tangled evolution. Ackerley concentrates on Watt's disconcerting difficulties and the textual errors that have further obscured a true understanding of the work.